Development of Natural-Based Bone Cement for a Controlled Doxorubicin-Drug Release - Dewhurst, Rebecca Marie; Scalzone, Annachiara; Buckley, Joseph; Mattu, Clara; Rankin, Kenneth S.; Gentile, Piergiorgio; Ferreira, Ana Marina (Frontiers in Bioengineering and Biotechnology, 2020)
Osteosarcoma (OS) accounts for 60% of all global bone cancer diagnoses. Intravenous administration of Doxorubicin Hydrochloride (DOXO) is the current form of OS treatment, however, systemic delivery has been linked to the onset of DOXO induced cardiomyopathy. Biomaterials including calcium phosphate cements (CPCs) and nanoparticles (NPs) have been tested as localized drug delivery scaffolds for OS cells. However, the tumour microenvironment is critical in cancer progression, with mesenchymal stem cells (MSCs) thought to promote OS metastasis and drug resistance. The extent of MSC assisted survival of OS cells in response to DOXO delivered by CPCs is unknown. In this study, we aimed at investigating the effect of DOXO release from a new formulation of calcium phosphate-based bone cement on the viability of OS cells cocultured with hMSC in vitro. NPs made of PLGA were loaded with DOXO and incorporated in the formulated bone cement to achieve local drug release. The inclusion of PLGA-DOXO NPs into CPCs was also proven to increase the levels of cytotoxicity of U2OS cells in mono- and coculture after 24 and 72 hours. Our results demonstrate that a more effective localized DOXO delivery can be achieved via the use of CPCs loaded with PLGA-DOXO NPs compared to CPCs loaded with DOXO, by an observed reduction in metabolic activity of U2OS cells in indirect coculture with hMSCs. The presence of hMSCs offer a degree of DOXO resistance in U2OS cells cultured on PLGA-DOXO NP bone cements. The consideration of the tumour microenvironment via the indirect inclusion of hMSCs in this study can act as a starting point for future direct coculture and in vivo investigations.